Universal Screening for Hypothyroidism in 1st Trimester of Pregnancy: Where are We for Subclinical Hypothyroidism? - Shrestha, Subha; Shrestha, Buddhi Kumar; Acharya, Manisha; Baniya, Puja; Kayastha, Bhagirathi; Lamsal, Sabin; Lekhak, Prateek; Khatiwada, Praju (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Subclinical hypothyroidism is missed to diagnose until fetal/maternal complications supervene and yet treatable if diagnose in 1st trimester. High disease prevalence and adverse pregnancy outcome concerns its timely identification & treatment to prevent, decrease or reverse the forthcoming complications. The objective of this research is to find prevalence of Subclinical hypothyroidism estimating TSH as 1st line test. Methods It was a descriptive cross sectional study. Sample size consisted of 153 pregnant women attending antenatal clinic & wards. TSH assessment was done at 1st visit along with antenatal testing. If TSH is ≥4mIu/ml (ATA) and ≥2.5mIU/ml (Iodine deficit area), freeT4 and thyroid perioxidase antibody test (anti-TPO) was further analyzed. Data was analyzed by using SPSS-20. Results A study was conducted among 153 pregnant women during their 1st trimester in the department of Obstetrics and Gynecology, College of Medical Sciences, Bharatpur, Nepal. The mean ±SD age was 26.1 ±4.38 years, mean ±SD gestational age was 7.6±1.35 weeks and mean ±SD body mass index (BMI) was 23.1±2.46. Thirteen percent subjects had TSH ≥4 mIU/L & 35% had TSH≥2.5mIU/ml above the cutoff used for definition of hypothyroidism. Anti Thyroid perioxidase (Anti-TPO) test positive were 47.6% (TSH≥4mIU/ml) Conclusions Subclinical hypothyroidism is highly prevalent in population visiting our hospital, so a universal screening with TSH estimation will be cost worthy in our area to intervene early before feto/maternal complications supervene.